COMMUNICATION OF ORGANIZATIONAL MANAGEMENT IN MORALITY AND TRANSPARENCY IN ADMINISTRATION OF THE TOWN MUNICIPALITY - Thaneto, Kunnida; Sridee, Supaporn; Boonsiri, Karn; Thamwipat, Kuntida (Journal of MCU Nakhondhat, 2025)
This research aimed to examine: 1) Policy communication and its driving role in organizational management for integrity and transparency in municipal administration, 2) Communication processes in organizational management for integrity and transparency, and 3) Strategies for developing communication to strengthen integrity and transparency in municipal administration. The study employed a mixed-method design. The qualitative component collected data through in-depth interviews with 33 key informants, including executives, personnel, staff, citizens, and communication scholars. The quantitative component collected data through surveys of municipal officials from Bang Rachan Municipality, Sing Buri Province (54 respondents), Wang Nam Yen Municipality, Sa Kaeo Province (78 respondents), and Chanthaburi Municipality, Chanthaburi Province (98 respondents), totaling 230 respondents. Data were analyzed using frequency distribution, percentage, mean, and standard deviation. The findings revealed that: 1) Policy communication for transparency serves as a foundation for building trust and reducing organizational conflict, with leadership and technology acting as supporting factors. 2) Communication processes emphasized the role of the sender, particularly municipal executives, who must demonstrate credibility and strong communication skills, while staff played roles as receivers and transmitters of information. Messages needed to be accurate, clear, and verifiable, and communication media should be diverse, including official documents, public relations materials, and digital platforms and 3) Developmental approaches - Suggested strategies include 1) Promoting participation of staff and citizens in formulating and communicating integrity and transparency policies, with a clear policy communication framework, and 2) Fostering learning exchanges among municipalities through networks and forums, such as a “Model Municipality for Integrity,” to support continuous development of municipal administration with integrity and transparency.